Study of the Prevalence of Obesity and Its Association with Maternal and Neonatal Characteristics and Morbidity Profile in a Population of Moroccan Pregnant Women - Fatima Taoudi; Fatima Zahra Laamiri; Fatima Barich; Nadia Hasswane; Hassan Aguenaou; Amina Barkat (Journal of Nutrition and Metabolism)
Obesity is a real public health problem whose prevalence continues to increase throughout the world. It affects all age groups and does not spare pregnant women. This work aims to determine the prevalence of obesity and to study its association with maternal and neonatal characteristics and the morbidity profile of pregnancy. This is a descriptive and cross-sectional study carried out in the maternity ward of the prefectural hospital center called “Sidi Lahcen” in Témara, Morocco, over a 12-month period. Maternal and neonatal data are collected through a preestablished questionnaire, and anthropometric parameters were recorded. 390 participants, aged between 18 and 43 years, were included in this study, with a prevalence of overweight and obesity of 34.9% and 41%, respectively. Correlation results revealed that the prevalence of overweight and obesity was significantly elevated in women over 25 years p<0.001. The rate of caesarean section was four times higher in obese women compared to women of normal weight (53.8% versus 12.8%; p=0.018). The over-term was significantly high in the obese group compared to the nonobese group (33.8% versus 20.2%; p=0.013). A statistically significant positive correlation was found between gestational body mass index and newborn birth weight (r = 0.29; p<0.001) as well as a high prevalence of macrosomia in newborns of comparatively obese women compared to newborns of nonobese women (17.6% versus 9.6%; p=0.041). The correlation analysis with the morbidity profile showed a significantly high preponderance of gestational diabetes, anemia, and toxemia of pregnancy in the obese group compared to the normal group p<0.001. This study clearly demonstrated that obesity during pregnancy is associated with higher risks of maternal and neonatal complications, the management of which places a burden on the health system as well as families. These data reinforce the need to improve antenatal care for the prevention of obesity and its preventable complications.